2015
DOI: 10.1111/1552-6909.12750
|View full text |Cite
|
Sign up to set email alerts
|

Commitment to Breastfeeding in the Context of Phenylketonuria

Abstract: Findings demonstrate the importance mothers attribute to breastfeeding and their willingness to invest considerable effort to breastfeed. Health care providers working with these mothers should help them strategize for success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Infant conditions generally caused hypotonia, somnolence and poor weight gain in a cluster or drove a need for feeding adaptations such as frequent short feeds and strategies to increase calories to manage fatigue and growth problems. Banta‐Wright et al (2015) was the exception to the previously mentioned adaptations to feeding. In their study, they found that mothers had to be constantly flexible, in response to their child's phenylalanine (Phe) levels, not because of their infant's tone or somnolence, but because of their underlying metabolic condition.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Infant conditions generally caused hypotonia, somnolence and poor weight gain in a cluster or drove a need for feeding adaptations such as frequent short feeds and strategies to increase calories to manage fatigue and growth problems. Banta‐Wright et al (2015) was the exception to the previously mentioned adaptations to feeding. In their study, they found that mothers had to be constantly flexible, in response to their child's phenylalanine (Phe) levels, not because of their infant's tone or somnolence, but because of their underlying metabolic condition.…”
Section: Resultsmentioning
confidence: 96%
“…A total of nine papers commented that lack of specialist lactation support made breastfeeding harder. For example, Banta‐Wright et al (2015) found that although there were designated International Board Certified Lactation Consultants (IBCLCs) in the neonatal unit, they were not employed in paediatrics. One study participant telephoned every IBCLC she knew to ask for information and managed through this convoluted route to get the help she needed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations